Personalized dendritic cell vaccine in multimodal individualized combination therapy improves survival in high-risk pediatric cancer patients - Kyr, Michal; Mudry, Peter; Polaskova, Kristyna; Dubska, Lenka Zdrazilova; Demlova, Regina; Kubatova, Jana; Hlavackova, Eva; Pilatova, Katerina Cerna; Mazanek, Pavel; Vejmelkova, Klara; Dusek, Vitezslav; Tinka, Pavel; et al. (International journal of cancer, 2024)
A lot of hope for high-risk cancers is being pinned on immunotherapy but the evidence in children is lacking due to the rarity and limited efficacy of single-agent approaches. Here, we aim to assess the effectiveness of multimodal therapy comprising a personalized dendritic cell (DC) vaccine in children with relapsed and/or high-risk solid tumors using the N-of-1 approach in real-world scenario. A total of 160 evaluable events occurred in 48 patients during the 4-year follow-up. Overall survival of the cohort was 7.03 years. Disease control after vaccination was achieved in 53.8% patients. Comparative survival analysis showed the beneficial effect of DC vaccine beyond 2 years from initial diagnosis (HR = 0.53, P = .048) or in patients with disease control (HR = 0.16, P = .00053). A trend for synergistic effect with metronomic cyclophosphamide and/or vinblastine was indicated (HR = 0.60 P = .225). A strong synergistic effect was found for immune check-point inhibitors (ICIs) after priming with the DC vaccine (HR = 0.40, P = .0047). In conclusion, the personalized DC vaccine was an effective component in the multimodal individualized treatment. Personalized DC vaccine was effective in less burdened or more indolent diseases with a favorable safety profile and synergized with metronomic and/or immunomodulating agents.
Keywords: individualizovaná medicína; Administration, Metronomic; Immune Checkpoint Inhibitors; Cyclophosphamide; Female; Infant; dítě; kombinovaná terapie; předškolní dítě; ženské pohlaví; Dendritic Cells; Neoplasms; dendritické buňky; nádory; Adolescent; Cancer Vaccines; Immunotherapy; lidé; následné studie; protinádorové vakcíny; inhibitory kontrolních bodů; Follow-Up Studies; Male; imunoterapie; kojenec; Combined Modality Therapy; Child, Preschool; Child; Precision Medicine; metronomické podávání léků; mužské pohlaví; vinblastin; cyklofosfamid; mladiství; Vinblastine; Humans